2023
DOI: 10.3389/fimmu.2022.1098725
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation, immunity, and oxidative stress in hypertension: New insights and potential therapeutic targets

Abstract: Hypertension is regarded as the most prominent risk factor for cardiovascular diseases, which have become a primary cause of death, and recent research has demonstrated that chronic inflammation is involved in the pathogenesis of hypertension. Both innate and adaptive immunity are now known to promote the elevation of blood pressure by triggering vascular inflammation and microvascular remodeling. For example, as an important part of innate immune system, classically activated macrophages (M1), neutrophils, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 164 publications
1
52
0
1
Order By: Relevance
“…It is worth mentioning that inflammatory markers such as PTX3, leptin, PDL1, and E-cadherin did not exhibit differences between the two groups during this phase. The lack of significant changes in inflammatory markers during the acute phase contradicts some reports associating hypertension with inflammation (5,37). This discrepancy may be due to the specific context of nephrotic syndrome, which could have unique inflammatory pathways.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is worth mentioning that inflammatory markers such as PTX3, leptin, PDL1, and E-cadherin did not exhibit differences between the two groups during this phase. The lack of significant changes in inflammatory markers during the acute phase contradicts some reports associating hypertension with inflammation (5,37). This discrepancy may be due to the specific context of nephrotic syndrome, which could have unique inflammatory pathways.…”
Section: Discussionmentioning
confidence: 60%
“…The origin of hypertension in NS is multifactorial, encompassing sodium retention, impaired kidney function, albuminuria, genetic predisposition, and medication side effects (4). Although inflammation and oxidative stress are linked to hypertension and its related conditions (5,6), the particular influence of hypertension on inflammation and oxidative stress in NS patients, despite the high prevalence of hypertension in this population, has not been examined. Understanding these connections could identify novel therapeutic targets and inform tailored interventions to mitigate the adverse effects of hypertension in NS patients.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , the serum TNF‐α, IL‐1β, and IL‐17 levels in the MI rats treated with ITE were significantly decreased compared with those in the MI group ( P < 0.05) ( Figure ), and up‐regulation of serum IL‐10 was observed in MI rats treated with ITE, but ITE treatment alone or sham surgery did not affect these levels. M1‐type macrophages are usually considered proinflammatory macrophages, while M2‐type macrophages are anti‐inflammatory macrophages 18 . Previous studies 13 have shown that ITE can inhibit inflammation by affecting macrophage polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, low HDL cholesterol levels may also affect blood circulation(36), which can impact the blood supply to the vestibular system. Secondly, hypertension and low HDL cholesterol levels may trigger in ammation responses (37)(38)(39), which can also cause damage to vestibular tissues and affect vestibular function (40,41). Lastly, it is possible that hypertension and low HDL cholesterol levels affect neurotransmitter secretion and function (42), thereby in uencing vestibular function (43).…”
Section: Discussionmentioning
confidence: 99%